Mnemonic regulation of sadness and anger: The role of spontaneous vs instructed recall - Oner, Sezin; Kaya-Kiziloz, Burcu (Springer, 2024)
Mood-incongruency effects in autobiographical recall have been conceptualized as a function of the emotion regulation through which the content and the phenomenology of the autobiographical memories serve to repair negative moods. Arguing that negative mood automatically activates mnemonic emotion regulation, in the present study we examined how negative emotions guide the subsequent spontaneous and instructed recall and whether distinct phenomenological patterns are observed in mnemonic regulation of sadness and anger. After participants watched video clips for sadness, anger, or happiness, they reported first any event that comes to their mind (spontaneous recall), then an event that specifically makes them happy (instructed recall). We found the changes in the phenomenology of the reported events was different for sadness and anger groups. While more robust changes were observed for sadness earlier in the spontaneous recall with higher phenomenological ratings than the anger group, in the instructed recall the difference disappeared, suggesting for the relatively late-onset compensation in the anger group.
Keywords: Autobiographical memory; Emotion regulation; Mood incongruence; Phenomenology